Sexual behaviour among young Danes aged 15–29 years: a cross-sectional study of core indicators. (21st January 2015) - Jørgensen, Marianne Johansson; Maindal, Helle Terkildsen; Christensen, Kaj Sparle; Olesen, Frede; Andersen, Berit
Abstract : Objectives: Sexually transmitted infections and unwanted pregnancies occur at high rates among youth. Understanding sexual behaviour is essential for planning and implementing future effective preventive interventions. The present study examines the sexual behaviour in the general Danish population aged 15–29 years using the core indicators recommended by the European Centre for Disease Prevention and Control. Methods: A nationwide cross-sectional study was conducted in Denmark among a random sample of 20 000 men and women in 2012. Respondents completed a web-based sexual behaviour questionnaire and data were linked to a nationally held demographic database. Core indicators for sexual behaviour frequency stratified by gender are presented as unweighted and weighted data after consideration of sociodemographic differences between respondents and non-respondents. Results: Response rate was 20.4%. Condoms were used at sexual debut by 69.9% of women and 62.3% of men, while 14.3% of women and 15.1% of men used no contraceptives at sexual debut. Half of the respondents used condom alone at the latest sexual encounter with a steady partner (women 51.8%, men 55.2%), while 10% used no contraceptives. Having a sexual encounter with a casual partner decreased the likelihood of using condoms (women 43.7%, men 49.5%) and increased the likelihood of using no contraceptives (women 14.8%, men 20.9%). Data on sexual behaviour characteristics showed only minor changes when weighted for non-response. Conclusions: The findings call for interventions addressing the use of appropriate contraception at sexual debut and at last sexual encounter; this seems particularly important when the sexual partner is a casual partner.